Implication of government failure to include palliative care medicine in medical colleges - Salihu, Sani Ibrahim; Yusof, Yuhanis; Halim, Rohizan; Mustapha, Aliyu (2016)
Medical profession like all other professions cannot be effectively practiced without code of ethics.Palliative care has been identified as the best treatment for terminally ill patient and a better alternative to euthanasia and assisted suicide.In Nigeria, Cancer and kidney failure are two serious terminal illnesses that present difficult situation, however, doctors are produced on yearly basis without palliative care training and euthanasia is strictly illegal.The objective of this paper is to bring out the implication of government failure for not having Nigerian doctors trained in palliative care medicine and strongly suggest the way forward.Empirical research method is used where in depth interview was conducted with three medical doctors.Findings shows terminally ill patient suffer seriously for lack of skilled doctors on Palliative care and pain management.